Association Between Visit-to-Visit Mean Arterial Pressure Variability and the Risk of Ischemic Heart Disease and Ischemic Stroke Among Patients With Hypertension in Thailand - Boonsub Sakboonyarat; Jaturon Poovieng; Ram Rangsin (Clinical Medicine Insights: Cardiology)
Background: Blood pressure (BP) variability has been recognized as a significant risk factor for cardiovascular diseases (CVD). We aim to evaluate the association between mean arterial pressure (MAP) variability and the increased risk of ischemic heart disease (IHD) and ischemic stroke (IS) among hypertensive patients in Thailand. Methods: We analyzed data from the Thailand DM/HT study, which included hypertensive patients nationwide in 2014 to 2015 and 2018. MAP variability was computed based on the MAP values across 3 visits within 1 year and expressed as standard deviation (SD). We used multivariable log-binomial regression models to evaluate the associations between MAP variability and the risk of IHD and IS. Results: Among 92 854 individuals, 594 new-onset IHD events (0.64%) and 187 IS incidents among 95 486 individuals (0.20%). Compared to the lowest quartile (Q1), higher quartiles of SD were associated with increased risk of IHD, with adjusted risk ratios (aRRs) of 1.06 (95% confidence interval [CI]: 0.82-1.38) for Q2, 1.35 (95% CI: 1.06-1.72) for Q3, and 1.50 (95% CI: 1.18-1.90) for Q4. Similarly, higher SD quartiles raised the risk of IS, with aRRs of 1.35 (95% CI: 0.83-2.20) for Q2, 1.56 (95% CI: 0.98-2.48) for Q3, and 1.97 (95% CI: 1.26-3.07) for Q4, when compared to Q1. Conclusion: Our study demonstrated that higher visit-to-visit MAP variability in hypertensive patients was strongly associated with an increased risk of CVD. We emphasize the importance of incorporating BP variability into management strategies to help reduce the risk of CVD in these patients.